Analysis Of Marketing Functions And Factors Influencing Soybean Marketing In Bantul Regency - Meyga Putri Nofianingsih; Nia Rosiana; Andriyono Kilat Adhi (Faculty of Animal and Agricultural Science, Diponegoro University, 2025)
Soybeans are one of the grains rich in vegetable fat and protein that have become one of the staples for the people of Indonesia. Indonesia has an important role in soybean production, which is an important commodity for food securityand the country's economy. Indonesia is the largest soybean market in Asia by importing 1.96 million tons of domesticsoybean needs. While the rest is produced through domestic soybean production. The purpose of this study was to analyze the function of soybean marketing and see what factors influence the selection of soybean marketing channels in Bantul Regency. The data analysis method was carried out using a qualitative descriptive analysis method to see the function of soybean marketing, and quantitative to see the factors that influence soybean marketing which were analyzed using multinominal logit. Farmers carry out marketing functions of purchasing, selling, transporting, milling, sorting, loading and unloading, packaging, drying, market information and risk. For the physical functions carried out by farmers are the functions of selling, transporting, milling, sorting, packaging, drying, market information, and risk. Marketing institutions also perform marketing functions including, 1) exchange function, namely purchase and sale function, 2) physical function, namely transportation, sorting, loading and unloading, and packaging, 3) facility function, namely market and risk information. Factors that influence farmers in choosing soybean marketing channels in Bantul Regency are farming experience, production volume, price, capital, land area, and rainy and dry seasons.